A Survey of Data Mining Techniques on Information Networks - Kodali, Sadhana; Dabbiru, Madhavi; Rao, B Thirumala (International Journal of Engineering and Technology, 2018)
An Information Network is the network formed by the interconnectivity of the objects formed due to the interaction between them. In our day-to-day life we can find these information networks like the social media network, the network formed by the interaction of web objects etc. This paper presents a survey of various Data Mining techniques that can be applicable to information networks. The Data Mining techniques of both homogeneous and heterogeneous information networks are discussed in detail and a comparative study on each problem category is showcased.
Keywords: InformationNetworks; DataMining Techniques; Homogeneous Information Networks; HeterogeneousInformation Networks